Correction to: The recurrent missense mutation p.(Arg367Trp) in YARS1 causes a distinct neurodevelopmental phenotype (Journal of Molecular Medicine, (2021), 10.1007/s00109-021-02124-9) - Averdunk, Luisa; Sticht, Heinrich; Surowy, Harald; Luedecke, Hermann-Josef; Koch-Hogrebe, Margarete; Alsaif, Hessa S.; Kahrizi, Kimia; Alzaidan, Hamad; Alawam, Bashayer S.; Tohary, Mohamed; Kraus, Cornelia; Endele, Sabine; et al. (Journal of Molecular Medicine, 2021)
In the published original paper, Fig. 1 is incomplete. Only Fig. 1a is shown. This erratum corrects Fig. 1 and adds the missing panel 1 b-f to the article.
CRIS-Team Scopus Importer:2021-10-29